Rapid evaluation of coaxiality of shaft parts based on double maximum material requirements. (December 2019) - Tang, Zhemin; Huang, Meifa; Sun, Yonghou; Zhong, Yanru; Qin, Yuchu
Highlights: Coaxiality-DMMR error could be verified with an adapted virtual gauge (AVG). An AVG consists of two coaxial shrinking cylindrical boundaries. The shrinking depends on the contact points of the measurements. The generation and motion of contact points can be solved as linear problems. The proposed method is more than 3.8 times faster than classic optimization method. Abstract: Simultaneous application of the maximum material requirements on the datum and coaxiality tolerances (referred to as DMMR coaxiality) of shaft parts can ensure assembly and reduce costs. Existing DMMR coaxiality evaluations use either inflexible real functional gauges or slow mathematical methods, which limits the applications of such a good tolerance in industry. This paper investigated a fast mathematical evaluation method for DMMR coaxiality. First, according to ISO requirements, the geometry and utility of the real functional gauge were analyzed. Then, an adaptive virtual gauge (AVG) was established, and the geometric structure and motion of the AVG were analyzed. After that, the mathematical evaluation method of the DMMR coaxiality tolerance was provided with uncertainty analysis. Finally, an exemplary application on a stepped shaft was presented, and the accuracy and speed of the method were reflected and improved by comparison with existing methods.